The Issue of Evidentiary Value in Integrated Forensic Investigations - D. A. Kudryashov (Теория и практика судебной экспертизы, 2016)
The paper looks at integrated forensic inquiry as a source of evidence in crime detection and investigation. This includes various aspects of assessing the findings of integrated forensic investigation in terms of evidence quality by the party bearing the burden of proof. A list of the most common organizational and procedural errors committed by the party with the burden of proof when requesting and conducting integrated forensic investigation is also examined.